Tedizolid Activity Against Clinical Mycobacterium abscessus Complex Isolates—An in vitro Characterization Study - Tang, Ying Wei; Cheng, Bernadette; Yeoh, Siang Fei; Lin, Raymond T. P.; Teo, Jeanette W. P. (Frontiers in Microbiology, 2018)
Mycobacterium abscessus complex consist of three rapidly growing subspecies: M. abscessus, M. massiliense and M. bolletii. They are clinically important human pathogens responsible for opportunistic pulmonary and skin and soft tissue infections. Treatment of M. abscessus infections is difficult due to in vitro resistance to most antimicrobial agents. Tedizolid (TZD) is a next-generation oxazolidinone antimicrobial with a wide spectrum of activity even against multidrug resistant Gram-positive bacteria. In this study, the in vitro activity of TZD against the M. abscessus complex (n=130) was investigated. Susceptibility testing by broth microdilution showed lower TZD minimum inhibitory concentrations (MICs) when compared to linezolid. The MIC50 and MIC90 was 1 mg/L and 4mg/L, respectively across all M. abscessus complex members, reflecting no difference in subspecies response to TZD. Pre-exposure of M. abscessus complex to subinhibitory concentrations of TZD did not trigger any inducible drug resistance. Single-drug time kill assays and bactericidal activity assays demonstrated bacteriostatic activity of TZD in all three M. abscessus subspecies, even at high drug concentrations of 4 to 8x MIC. Combination testing of TZD with clarithromycin, doxycycline and amikacin using the checkerboard approach showed no antagonistic interactions. TZD may be an effective therapeutic antimicrobial agent for the treatment of M. abscessus infections.